Develop earthquake system for safety using wireless sensor network - Mohd Saffwan, Mohd Reip (2018)
As a contrasting option to current wired-based networks, wireless sensor networks (WSNs) are turning into an inexorably convincing stage for monitoring building structure because of generally minimal effort, simple establishment, thus forth. However, there is as yet an unaddressed test which is the application-particular trustworthiness regarding sensor fault identification and tolerance. The reliability is additionally influenced by a lessening on the nature of checking while relieving WSN obliges. This can be created by deficiencies in sensor holding, accuracy corruption, intensification increase, inclination, float, commotion, et cetera. This venture is concentrating on observing information transmission in wireless sensor system to guarantee the unwavering quality of structural health checking by proposing another strategy for system.